Lithium ion secondary battery, preparation method thereof and electric device

By using inorganic material modified polyacrylate binder in the positive electrode sheet of the lithium-ion secondary battery, the problems of high internal resistance and poor kinetic performance of the lithium-ion secondary battery are solved, and the lower internal resistance and Combination of good kinetic properties.

CN119153702AActive Publication Date: 2024-12-17CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411625264.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2024-12-17
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

When a lithium-ion secondary battery with lithium-containing phosphate as the positive electrode active material is used with polyacrylate binder, its internal resistance is large and its kinetic performance is poor, and it is necessary to reduce the internal resistance and improve the kinetic performance.

Method used

Modified polyacrylate binder with inorganic materials. By grafting the polyacrylate polymer on the surface of inorganic particles, the agglomeration of inorganic particles is avoided, so that the inorganic particles are evenly dispersed, and the polyacrylate binder is inhibited from being in the The lithium-containing phosphate material forms a film on the surface to speed up the transmission of lithium ions.

Benefits of technology

It effectively reduces the internal resistance of lithium-ion secondary batteries, improves the dynamic performance of the battery, and takes into account the mechanical properties of the positive electrode sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153702A_ABST
    Figure CN119153702A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion secondary battery, a preparation method thereof and a power utilization device, the lithium ion secondary battery comprises a positive pole piece, the positive pole piece comprises a positive active material layer, and the positive active material layer comprises lithium-containing phosphate and an inorganic material modified polyacrylate binder; the inorganic material modified polyacrylate binder comprises a polyacrylate polymer and inorganic particles, and at least part of the polyacrylate polymer is grafted on the surfaces of the inorganic particles; the polyacrylate polymer comprises a structural unit derived from an acrylate monomer. The inorganic material modified polyacrylate binder is added into the positive electrode active material layer taking lithium-containing phosphate as a positive electrode active material, so that the lithium ion secondary battery has relatively low internal resistance and relatively good dynamic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a lithium-ion secondary battery and a preparation method and an electrical device thereof. Background Art

[0002] In recent years, as the application scope of secondary batteries becomes wider and wider, secondary batteries are widely used in energy storage power supply systems such as hydropower, thermal power, wind power and solar power stations, as well as in many fields such as electric tools, electric bicycles, electric motorcycles and electric vehicles.

[0003] Lithium-ion secondary batteries using lithium-containing phosphates such as lithium iron phosphate (LFP) as positive electrode active materials have the advantages of low cost and good safety, and have become a hot area for the development of lithium-ion secondary batteries. PVDF (polyvinylidene fluoride) is usually used as a binder in positive electrode sheets using lithium-containing phosphates as positive electrode active materials. However, due to considerations such as persistent pollution risks and bioaccumulative hazards, the use of fluorine-containing PVDF binders needs to be restricted. Polyacrylate binders with strong bonding strength and good stability can usually be used instead of PVDF.

[0004] However, the internal resistance (DCR) of lithium-ion secondary batteries using lithium-containing phosphate as the positive electrode active material and polyacrylate binder is usually relatively large, and the dynamic performance of the battery is poor. Therefore, how to reduce the internal resistance of such lithium-ion secondary batteries and improve their dynamic performance has become one of the key areas of concern for those skilled in the art. Summary of the invention

[0005] The present application is made in view of the above-mentioned problems, and one of its purposes is to provide a lithium-ion secondary battery with low internal resistance and good dynamic performance, and correspondingly provides a preparation method and an electrical device of the lithium-ion secondary battery.

[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a lithium-ion secondary battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises a lithium-containing phosphate and an inorganic material-modified polyacrylate binder;

[0007] The inorganic material modified polyacrylate binder comprises a polyacrylate polymer and inorganic particles, at least a portion of the polyacrylate polymer is grafted onto the surface of the inorganic particles; the polyacrylate polymer comprises a structural unit derived from an acrylic acid ester monomer.

[0008] By using the above-mentioned inorganic material to modify the polyacrylate binder, at least a portion of the polyacrylate polymer is grafted onto the surface of the inorganic particles, so that the agglomeration of the inorganic particles can be avoided, the inorganic particles can be evenly dispersed in the binder, and the inorganic particles can effectively inhibit the polyacrylate binder from forming a film on the surface of the lithium phosphate material, reduce the density of the polyacrylate binder film on the surface of the lithium phosphate material, accelerate the transmission of lithium ions, thereby reducing the internal resistance of the lithium ion secondary battery and improving the dynamic performance of the battery.

[0009] In any embodiment, the acrylic acid ester monomer includes one or more of methyl methacrylate, butyl acrylate or isooctyl acrylate.

[0010] In any embodiment, the mass proportion of the structural unit derived from the acrylic acid ester monomer in the polyacrylate polymer is 60% to 80%.

[0011] In any embodiment, the polyacrylate polymer further comprises a structural unit derived from a first monomer, wherein the first monomer comprises one or more of styrene or acrylonitrile. This is beneficial to improving the cohesive force of the positive electrode sheet.

[0012] In any embodiment, the mass proportion of the structural unit derived from the non-polar monomer in the polyacrylate polymer is 20% to 40%.

[0013] In any embodiment, the inorganic particles include one or more of titanium dioxide (TiO2), silicon dioxide (SiO2), calcium stearate or aluminum oxide (Al2O3). In this way, the polyacrylate binder can be effectively inhibited from forming a film on the surface of the lithium-containing phosphate material, reducing the density of the film, accelerating the transmission of lithium ions, and thus reducing the internal resistance of the battery and improving the dynamic performance of the battery. In addition, the above-mentioned inorganic particles have good inertness and will not have a negative impact on the positive electrode active material.

[0014] In any embodiment, the weight average molecular weight of the polyacrylate polymer is 150,000 Daltons to 400,000 Daltons. This is beneficial to improving the mechanical properties of the positive electrode sheet, such as adhesion and cohesion, and the processing performance of the positive electrode slurry is good.

[0015] In any embodiment, the mass fraction of the inorganic particles in the inorganic material modified polyacrylate binder is 5% to 20%. This is beneficial for reducing the internal resistance of the battery and improving the battery dynamics while taking into account the mechanical properties of the positive electrode sheet.

[0016] In any embodiment, the mass fraction of the inorganic particles in the inorganic material modified polyacrylate binder is 10% to 15%. This is conducive to better balance the battery kinetic performance and the mechanical properties of the positive electrode sheet. The battery has a lower internal resistance and better kinetic performance, while the positive electrode sheet has good mechanical properties.

[0017] In any embodiment, based on the total mass of the positive electrode active material layer being 100%, the mass fraction of the inorganic material modified polyacrylate binder is 1% to 2%. This is conducive to making the positive electrode slurry have better dispersibility, improving the mechanical properties of the positive electrode sheet, and having less adverse effects on the battery energy density.

[0018] In any embodiment, the positive electrode active material layer further includes a dispersant, and the dispersant includes one or more of a phosphate dispersant or a styrene-ethylene / butylene-styrene block copolymer (SEBS) dispersant. This is beneficial to improve the dispersibility of the positive electrode slurry and the flexibility of the positive electrode sheet.

[0019] In any embodiment, based on the total mass of the positive electrode active material layer being 100%, the mass fraction of the dispersant is 0.1% to 0.5%, which is beneficial to effectively improve the dispersibility of the positive electrode slurry.

[0020] In any embodiment, based on the total mass of the positive electrode active material layer being 100%, the mass fraction of the dispersant is 0.3% to 0.5%, which is beneficial to further improve the dispersibility of the positive electrode slurry.

[0021] In any embodiment, based on the total mass of the positive electrode active material layer being 100%, the mass fraction of the lithium-containing phosphate is 95% to 99%.

[0022] In any embodiment, the lithium-containing phosphate includes one or more of lithium iron phosphate, lithium manganese phosphate or lithium manganese iron phosphate.

[0023] A second aspect of the present application provides a method for preparing a lithium ion secondary battery, comprising the following steps:

[0024] A lithium-containing phosphate, an inorganic material-modified polyacrylate binder and a solvent are mixed to obtain a positive electrode slurry; the inorganic material-modified polyacrylate binder comprises a polyacrylate polymer and inorganic particles, at least a portion of the polyacrylate polymer is grafted onto the surface of the inorganic particles; the polyacrylate polymer comprises a structural unit derived from an acrylic acid ester monomer;

[0025] The positive electrode slurry is placed on a positive electrode current collector and dried to obtain a positive electrode sheet; and

[0026] The positive electrode sheet, the separator and the negative electrode sheet are stacked so that the separator is disposed between the positive electrode sheet and the negative electrode sheet to obtain an electrode assembly, and the electrode assembly is made into a secondary battery.

[0027] By grafting polyacrylate polymers onto the surface of inorganic particles, the agglomeration of inorganic particles can be avoided, the inorganic particles can be evenly dispersed in the binder, and the inorganic particles can effectively inhibit the film formation of the polyacrylate binder on the surface of the lithium phosphate material, reduce the density of the film formed by the polyacrylate binder on the surface of the lithium phosphate material, accelerate the transmission of lithium ions, thereby reducing the internal resistance of the lithium ion secondary battery and improving the dynamic performance of the battery.

[0028] In any embodiment, the method for preparing the inorganic material modified polyacrylate binder comprises the following steps:

[0029] The inorganic particles are surface modified by using a silane coupling agent;

[0030] The surface-modified inorganic particles are mixed with acrylic ester monomers and initiators to obtain the inorganic material-modified polyacrylate binder after reaction.

[0031] In this way, the inorganic particles and the polyacrylate polymer material can be connected through chemical bonds, thereby improving the compatibility between the inorganic particles and the polyacrylate polymer, enhancing the binding force between the inorganic particles and the polyacrylate polymer material, avoiding the agglomeration of the inorganic particles, allowing the inorganic particles to be evenly dispersed in the binder, and enabling the inorganic particles to effectively inhibit the polyacrylate binder from forming a film on the surface of the lithium phosphate material.

[0032] In any embodiment, the silane coupling agent includes one or more of hexamethyldisilazane, γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane.

[0033] In any embodiment, the initiator is a free radical polymerization initiator, and the initiator includes one or more of potassium persulfate, azobisisobutyronitrile or benzoyl peroxide.

[0034] In any embodiment, the acrylic acid ester monomer includes one or more of methyl methacrylate, butyl acrylate or isooctyl acrylate.

[0035] In any embodiment, the inorganic particles include one or more of titanium dioxide, silicon dioxide, calcium stearate or aluminum oxide.

[0036] In any embodiment, the Dv50 particle size of the inorganic particles is 1 μm to 5 μm. This is beneficial for fully dispersing the inorganic particles in the emulsion during the preparation of the inorganic material modified polyacrylate binder.

[0037] The third aspect of the present application provides an electrical device, comprising one or more of the lithium ion secondary battery of the first aspect of the present application or the lithium ion secondary battery prepared by the preparation method of the lithium ion secondary battery of the second aspect of the present application.

[0038] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0040] Figure 1 A schematic diagram of a battery cell according to an embodiment of the present application;

[0041] Figure 2 for Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown;

[0042] Figure 3 A schematic diagram of an electrical device using a lithium-ion secondary battery according to an embodiment of the present application as a power source.

[0043] Description of reference numerals:

[0044] 5. Battery cell; 51. Shell; 52. Electrode assembly; 53. Cover plate; 6. Electrical device. DETAILED DESCRIPTION

[0045] Hereinafter, the lithium-ion secondary battery of the present application, its preparation method, and the implementation mode of the electric device are described in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0046] The "range" disclosed in the present application can be limited in the form of a lower limit and an upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The range limited in this way can be including or excluding end values, and any end value can be included or not included independently, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that the range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are also listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents the abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.

[0047] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0048] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0049] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.

[0050] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0051] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "comprise", etc., unless otherwise specified, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. Unless otherwise specified, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A not only includes a1, a2 and a3, but also includes other members". In the present application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0052] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.

[0053] At present, PVDF is usually used as a binder in the positive electrode sheets of batteries using lithium-containing phosphate as the positive electrode active material. However, due to the risk of persistent pollution and bioaccumulative hazards, the use of fluorine-containing PVDF binders needs to be restricted. Polyacrylate binders with strong bonding force and good stability can usually be used to replace PVDF. However, the internal resistance of lithium-ion secondary batteries using lithium-containing phosphate as the positive electrode active material and polyacrylate binders is usually relatively large, and the dynamic performance of the battery is poor.

[0054] Based on this, one embodiment of the present application provides a lithium-ion secondary battery, which includes a positive electrode plate, the positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes a lithium-containing phosphate and an inorganic material modified polyacrylate binder; the inorganic material modified polyacrylate binder includes a polyacrylate polymer and inorganic particles, at least a portion of the polyacrylate polymer is grafted on the surface of the inorganic particles; the polyacrylate polymer includes a structural unit derived from an acrylic ester monomer.

[0055] Traditional positive electrode sheets using lithium-containing phosphate as positive electrode active materials usually use PVDF as a binder. In some batteries using PFAS (per / polyfluoroalkyl substances, perfluorinated and polyfluoroalkyl substances), the use of PVDF needs to be restricted due to the risk of persistent pollution and bioaccumulative hazards. For example, polyacrylate binders with strong bonding force and good stability can be used instead of PVDF. However, the internal resistance (DCR) of lithium-ion secondary batteries containing lithium phosphate using polyacrylate binders is large and the dynamic performance is poor. The main reason is that the polar groups in the polyacrylate binder will form hydrogen bonds and other interactions with the polar sites (such as phosphate) on the surface of the lithium-containing phosphate, thereby forming a relatively dense binder film on the surface of the lithium-containing phosphate, and the polyacrylate binder itself has poor ion conductivity. The dense binder film wrapped on the surface of the lithium-containing phosphate material makes the internal resistance of the lithium-ion secondary battery large and the dynamic performance poor.

[0056] In the above-mentioned lithium-ion secondary battery, an inorganic material-modified polyacrylate binder is added to the positive electrode active material layer of the positive electrode plate; wherein, by grafting at least part of the polyacrylate polymer on the surface of the inorganic particles, the agglomeration of the inorganic particles can be avoided, so that the inorganic particles have good compatibility with the polyacrylate binder and can be evenly dispersed in the binder, so that the inorganic particles can effectively inhibit the polyacrylate binder from forming a film on the surface of the lithium-phosphate material, reduce the density of the polyacrylate binder film on the surface of the lithium-phosphate material, accelerate the transmission of lithium ions, thereby reducing the internal resistance of the lithium-ion secondary battery and improving the dynamic performance of the battery. wherein, the polyacrylate polymer is grafted on the surface of the inorganic particle, for example, the polyacrylate polymer can be connected to the surface of the inorganic particle by chemical bonding.

[0057] It should be noted that inorganic material modified polyacrylate polymers refer to, but are not limited to, connecting inorganic particles with polyacrylate polymers by physical or chemical methods. From a chemical perspective, it is to use the active functional groups (such as carboxyl, hydroxyl, etc.) on the molecular chain of polyacrylic polymers to react chemically with the active sites on the surface of inorganic particles (such as hydroxyl groups on the surface of metal oxide particles), so that the polymer chain is firmly "grafted" on the inorganic particles; from a physical perspective, in some cases, the polymer and inorganic particles can also be tightly combined through electrostatic interaction, adsorption, etc., so that the polymer is attached to the inorganic particles, achieving a similar grafting effect; whether the inorganic particles and polyacrylate binders in inorganic material modified polyacrylate binders are grafted can be judged by Fourier transform infrared spectroscopy (FT-IR). Specifically, if the inorganic particles and polyacrylate binders undergo a grafting reaction, new chemical bonds will be formed, and corresponding characteristic absorption peaks will appear in the infrared spectrum, or the position, intensity, and shape of some original absorption peaks will change. For example, inorganic particles usually have hydroxyl groups on their surfaces. After being grafted with polyacrylates, the absorption peak of the hydroxyl groups may shift or broaden. By comparing the infrared spectrum with that of polyacrylate binders to which inorganic particles have not been grafted, it is possible to determine whether a grafting reaction has occurred between the inorganic particles and the polyacrylate binder.

[0058] It can also be judged by scanning electron microscopy (SEM) combined with energy dispersive spectroscopy (EDS). Specifically, the surface morphology of the sample can be observed by scanning electron microscopy. If the inorganic particles are grafted with polyacrylate binders, in terms of microstructure, the inorganic particles will be relatively evenly dispersed in the polyacrylate binder and have a good bonding interface with the binder. Then, the elements on the surface of the sample can be qualitatively and quantitatively analyzed by energy dispersive spectroscopy, and the distribution of inorganic elements can be detected to determine whether the inorganic particles are grafted with the polymer. If it is found that the inorganic elements are evenly distributed in the binder and there is no obvious separation phenomenon at the interface, it can be determined that grafting has occurred.

[0059] In some of the embodiments, the inorganic particles are grafted with polyacrylate polymers through silane coupling agents. In this way, polyacrylate polymers can be grafted with inorganic particles through silane coupling agents, so that the polyacrylate polymers and inorganic particles are connected by chemical bonding (such as covalent bonds). Specifically, the silane coupling agent and inorganic particles are first mixed in a solvent, and the reaction is stirred to graft the silane coupling agent to the surface of the inorganic particles; then the surface-modified inorganic particles are added to the acrylate monomers, and an initiator is added for copolymerization. During the reaction, the silane coupling agent on the surface of the inorganic particles reacts with the polyacrylate polymer, thereby grafting the polyacrylate polymer to the surface of the inorganic particles. In some of the embodiments, the acrylate monomers include one or more of methyl methacrylate, butyl acrylate or isooctyl acrylate. The structural unit of the above-mentioned acrylate monomers is used in the binder, which has good bonding properties and is conducive to improving the mechanical properties of the pole piece.

[0060] In some embodiments, the mass proportion of the structural units derived from acrylate monomers in the polyacrylate polymer is 60% to 80%. It is understood that the mass proportion of the structural units derived from acrylate monomers in the polyacrylate polymer can be 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, and any value within the range formed by any two of the above values.

[0061] In some embodiments, the polyacrylate polymer further includes a structural unit derived from a first monomer, and the first monomer includes one or more of styrene or acrylonitrile. Thus, the structural unit derived from the first monomer is used in the polyacrylate polymer, styrene contains a benzene ring structure, and acrylonitrile contains a polar nitrile group. After polymerizing them with the acrylic ester monomer, the interaction sites between polymer molecules can be increased, so that the attraction between molecules is enhanced, and the bonding between polymer molecules is tighter, which is conducive to improving the cohesion.

[0062] In some embodiments, the mass proportion of the structural unit derived from the first monomer in the polyacrylate polymer is 20% to 40%. It is understood that the mass proportion of the structural unit derived from the first monomer in the polyacrylate polymer may be 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, and any value within the range formed by any two of the above values.

[0063] In some embodiments, the inorganic particles include one or more of titanium dioxide, silicon dioxide, calcium stearate or aluminum oxide. By using the above inorganic particles to modify the polyacrylate binder, the polyacrylate binder can be effectively inhibited from forming a film on the surface of the lithium-containing phosphate material, accelerating the transmission of lithium ions, thereby reducing the internal resistance of the battery and improving the dynamic performance of the battery. In addition, the above inorganic particles have good inertness in the positive electrode slurry, will not react with the positive electrode active material, and will not have a negative impact on the performance of the positive electrode active material.

[0064] In some embodiments, the weight average molecular weight of the polyacrylate polymer is 150,000 Daltons to 400,000 Daltons. Controlling the weight average molecular weight of the polyacrylate polymer within the above range is beneficial to improving the mechanical properties of the positive electrode sheet, and has good processing performance and is not prone to gelation.

[0065] It is understood that the weight average molecular weight of the polyacrylate polymer can be 150,000 Daltons, 160,000 Daltons, 170,000 Daltons, 180,000 Daltons, 190,000 Daltons, 200,000 Daltons, 210,000 Daltons, 220,000 Daltons, 230,000 Daltons, 240,000 Daltons, 250,000 Daltons, 260,000 Daltons, 270,000 Daltons, 280,000 Daltons, 290,000 Daltons, 300,000 Daltons, 310,000 Daltons, 320,000 Daltons, 330,000 Daltons, 340,000 Daltons, 350,000 Daltons, 360,000 Daltons, 370,000 Daltons, 380,000 Daltons, 390,000 Daltons, 400,000 Daltons and any value within the range formed by any two of the above values. It is understood that 10,000 Daltons is equal to 10 kDa.

[0066] In some embodiments, the mass fraction of inorganic particles in the inorganic material modified polyacrylate binder is 5% to 20%. Controlling the mass fraction of inorganic particles in the inorganic material modified polyacrylate binder within the above range is beneficial to reduce the internal resistance of the battery, improve the battery dynamics, and take into account the mechanical properties of the positive electrode sheet.

[0067] It can be understood that the mass fraction of inorganic particles in the inorganic material modified polyacrylate binder can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% and any value within the range formed by any two of the above values.

[0068] In some embodiments, the mass fraction of inorganic particles in the inorganic material modified polyacrylate binder is 10% to 15%. Controlling the mass fraction of inorganic particles in the inorganic material modified polyacrylate binder within the above range is conducive to better balancing the battery kinetic performance and the mechanical properties of the positive electrode sheet. The battery has lower internal resistance and better kinetic performance, while the positive electrode sheet has good mechanical properties.

[0069] In some embodiments, the mass fraction of the inorganic material modified polyacrylate binder is 1% to 2% based on the total mass of the positive electrode active material layer as 100%. Controlling the mass fraction of the inorganic material modified polyacrylate binder in the positive electrode active material layer within the above range is conducive to making the positive electrode slurry have better dispersibility, improving the mechanical properties of the positive electrode sheet, and will not significantly affect the energy density of the battery.

[0070] It can be understood that, based on the total mass of the positive electrode active material layer as 100%, the mass fraction of the inorganic material modified polyacrylate binder can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% and any value within the range formed by any two of the above values.

[0071] In some embodiments, the mass fraction of the inorganic material modified polyacrylate binder is 1% to 1.8% based on the total mass of the positive electrode active material layer as 100%. Further controlling the mass fraction of the inorganic material modified polyacrylate binder in the positive electrode active material layer within the above range is conducive to better balancing the dispersibility of the positive electrode slurry, the mechanical properties of the positive electrode sheet and the energy density of the battery.

[0072] In some embodiments, the positive electrode active material layer further includes a dispersant, and the dispersant includes a flexible dispersant. By adding a dispersant to the positive electrode active material layer, the positive electrode slurry using an inorganic material modified polyacrylate binder can be made less likely to gel and easier to process; by using a flexible dispersant, the positive electrode sheet using an inorganic material modified polyacrylate binder can maintain good flexibility, which is more conducive to making the positive electrode slurry less likely to gel and easier to process.

[0073] It can be understood that the flexible dispersant refers to a dispersant that can improve the flexibility of the positive electrode plate and promote the formation of a good dispersion effect of the polyacrylate binder in the positive electrode slurry.

[0074] In some embodiments, the dispersant includes one or more of a phosphate dispersant or a styrene-ethylene / butylene-styrene block copolymer (SEBS) dispersant. Phosphate dispersants and SEBS dispersants have certain flexibility and can well disperse inorganic material modified polyacrylate binders, which is beneficial to improving the dispersibility of the positive electrode slurry and the flexibility of the positive electrode sheet.

[0075] Among them, phosphate dispersants are organic compounds containing phosphate functional groups (-OPO(OR)2), where R represents an organic group. SEBS (Styrene Ethylenebutylene Styrene) dispersants are linear triblock copolymers, which are triblock copolymers with polystyrene as the terminal segment and ethylene-butylene copolymer obtained by hydrogenation of polybutadiene as the middle elastic block. It can be understood that the above-mentioned phosphate dispersants and SEBS dispersants can both use existing commercially available products.

[0076] In some of the embodiments, the mass fraction of the dispersant is 0.1% to 0.5%, based on the total mass of the positive electrode active material layer as 100%. Controlling the mass fraction of the dispersant in the positive electrode active material layer within the above range is conducive to improving the dispersibility of the positive electrode slurry. It is understood that the mass fraction of the dispersant in the positive electrode active material layer may be 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, 0.32%, 0.35%, 0.38%, 0.4%, 0.42%, 0.45%, 0.48%, 0.5% and any value within the range formed by any two of the above values.

[0077] In some embodiments, the mass fraction of the dispersant is 0.3% to 0.5% based on the total mass of the positive electrode active material layer as 100%. Further controlling the mass fraction of the flexible dispersant in the positive electrode active material layer within the above range is conducive to further improving the dispersibility of the positive electrode slurry.

[0078] In some embodiments, the mass fraction of the lithium-containing phosphate is 95% to 99% based on the total mass of the positive electrode active material layer as 100%. The lithium-containing phosphate may include one or more of lithium iron phosphate, lithium manganese phosphate or lithium manganese iron phosphate.

[0079] In one embodiment of the present application, a preparation method for the above-mentioned lithium-ion secondary battery is provided, and the preparation method comprises the following steps: mixing a lithium-containing phosphate, an inorganic material-modified polyacrylate binder and a solvent to obtain a positive electrode slurry; the inorganic material-modified polyacrylate binder comprises a polyacrylate polymer and inorganic particles, and at least a portion of the polyacrylate polymer is grafted onto the surface of the inorganic particles; the polyacrylate polymer comprises a structural unit derived from an acrylic ester monomer; the positive electrode slurry is disposed on a positive electrode collector and dried to obtain a positive electrode sheet; the positive electrode sheet, a separator and a negative electrode sheet are stacked and disposed so that the separator is disposed between the positive electrode sheet and the negative electrode sheet to obtain an electrode assembly, and the electrode assembly is made into a lithium-ion secondary battery.

[0080] By grafting polyacrylate polymers onto the surface of inorganic particles, the agglomeration of inorganic particles can be avoided, the inorganic particles can be evenly dispersed in the binder, and the inorganic particles can effectively inhibit the film formation of the polyacrylate binder on the surface of the lithium phosphate material, reduce the density of the film formed by the polyacrylate binder on the surface of the lithium phosphate material, accelerate the transmission of lithium ions, thereby reducing the internal resistance of the lithium ion secondary battery and improving the dynamic performance of the battery.

[0081] In some embodiments, the acrylic acid ester monomer includes one or more of methyl methacrylate, butyl acrylate or isooctyl acrylate.

[0082] In some of the embodiments, the preparation method of the above-mentioned inorganic material modified polyacrylate adhesive comprises the following steps: firstly, the inorganic particles are surface-modified by using a silane coupling agent; then, the surface-modified inorganic particles are mixed with an acrylate monomer and an initiator, and the inorganic material modified polyacrylate adhesive is obtained after a polymerization reaction.

[0083] The inorganic particles are surface-modified by a silane coupling agent and then polymerized to form a polyacrylate binder, which is conducive to connecting the inorganic particles with the polyacrylate polymer material through chemical bonds, improving the compatibility between the inorganic particles and the polyacrylate polymer material, and enhancing the binding force between the inorganic particles and the polyacrylate polymer material, which can avoid the agglomeration of the inorganic particles, and make the inorganic particles evenly dispersed in the binder, so that the inorganic particles can effectively inhibit the polyacrylate binder from forming a film on the surface of the lithium phosphate material. It can be understood that the inorganic material modified polyacrylate binder can also use existing commercially available products.

[0084] In some embodiments, the silane coupling agent includes one or more of hexamethyldisilazane, γ-aminopropyltriethoxysilane or γ-glycidyloxypropyltrimethoxysilane. The initiator is a free radical polymerization initiator, and the initiator includes one or more of potassium persulfate, azobisisobutyronitrile or benzoyl peroxide. The acrylate monomer includes one or more of methyl methacrylate, butyl acrylate or isooctyl acrylate.

[0085] In some of the embodiments, the surface of nano-SiO2 particles is first modified with hexamethyldisilazane (HMDS), then mixed with methyl methacrylate (MMA) and butyl acrylate (BA) emulsions to form a Pickering emulsion, and then reacted with an initiator potassium persulfate (KPS) to prepare a nano-SiO2 modified acrylate adhesive.

[0086] In some embodiments, the inorganic particles include one or more of titanium dioxide, silicon dioxide, calcium stearate or aluminum oxide. The use of the above inorganic particles to modify the polyacrylate binder is conducive to inhibiting the polyacrylate binder from forming a film on the surface of the lithium-containing phosphate material, accelerating the transmission of lithium ions, thereby reducing the internal resistance of the battery and improving the dynamic performance of the battery. In addition, the above inorganic particles have good inertness in the positive electrode slurry, will not react with the positive electrode active material, and will not have a negative impact on the performance of the positive electrode active material.

[0087] In some of the embodiments, the Dv50 particle size of the inorganic particles is 1 μm to 5 μm. Controlling the Dv50 particle size of the inorganic particles within the above range is conducive to the inorganic particles being fully dispersed in the emulsion during the preparation of the inorganic material-modified polyacrylate binder, and the filter element will not be blocked during subsequent filtration due to the excessive size of the inorganic particles. It is understandable that the Dv50 particle size of the inorganic particles can be 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5 μm and any value within the range formed by any two of the above values.

[0088] It should be noted that the Dv50 particle size is also called the median particle size, which refers to the particle size corresponding to when the cumulative particle size distribution percentage reaches 50% in a particle size distribution.

[0089] In one embodiment of the present application, a positive electrode plate is provided, which includes a positive electrode active material layer, wherein the positive electrode active material layer includes a lithium-containing phosphate and an inorganic material-modified polyacrylate binder; the inorganic material-modified polyacrylate binder includes a polyacrylate polymer and inorganic particles, and at least a portion of the polyacrylate polymer is grafted onto the surface of the inorganic particles.

[0090] By adding inorganic materials to the positive electrode active material layer of the positive electrode plate to modify the polyacrylate binder; by grafting the polyacrylate polymer on the surface of the inorganic particles, the inorganic particles can be evenly dispersed in the binder, which can effectively inhibit the polyacrylate binder from forming a film on the surface of the lithium phosphate material, accelerate the transmission of lithium ions, thereby reducing the internal resistance of the lithium ion secondary battery and improving the battery's dynamic performance.

[0091] In some embodiments, the positive electrode sheet further includes a positive electrode current collector, and the positive electrode active material layer is disposed on at least one side surface of the positive electrode current collector.

[0092] In one embodiment of the present application, a positive electrode slurry is provided, including a lithium-containing phosphate, an inorganic material-modified polyacrylate binder and an organic solvent; the inorganic material-modified polyacrylate binder includes a polyacrylate polymer and inorganic particles, and at least a portion of the polyacrylate polymer is grafted onto the surface of the inorganic particles.

[0093] In some of the embodiments, based on 100% dry weight of the positive electrode slurry, the mass fraction of the inorganic material modified polyacrylate binder is 0.5%-2%; and the mass fraction of the dispersant is 0.1%-0.5%.

[0094] In one embodiment of the present application, an electrical device is provided, which includes one or more of the lithium ion secondary batteries described above in the present application or the lithium ion secondary batteries prepared by the method for preparing the lithium ion secondary batteries described above in the present application.

[0095] The lithium ion secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.

[0096] In one embodiment of the present application, a lithium ion secondary battery is provided.

[0097] Generally, lithium-ion secondary batteries include a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0098] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.

[0099] As a non-limiting example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0100] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0101] In some embodiments, the positive electrode active material includes a lithium-containing phosphate, and may also include other positive electrode active materials for batteries known in the art. Non-limiting examples of lithium-containing phosphates may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0102] As non-limiting examples, other positive electrode active materials for batteries include lithium transition metal oxides and modified compounds thereof. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide and modified compounds thereof. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O4, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ) etc.; Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.85 Co 0.1 Al 0.05 O2.

[0103] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the content of Li in the positive electrode plate is different when the battery is discharged to different states. In the list of positive electrode materials in this application, unless otherwise specified, the content of Li is the initial state of the material. The positive electrode material is applied to the positive electrode plate in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode material contained in the plate usually changes. Among them, the content of Li can be measured by molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry. It is understandable that the new material obtained by appropriate modification on the basis of the listed positive electrode materials is also within the scope of the positive electrode material. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode material, and non-limiting examples include coating modification.

[0104] In the list of positive electrode materials in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by molar content, but is not limited to this.

[0105] The weight ratio of the positive electrode active material in the positive electrode active material layer is 80 wt % to 100 wt % based on the total weight of the positive electrode active material layer.

[0106] In some embodiments, the positive electrode active material layer may further include a conductive agent. As a non-limiting example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode active material layer is 0 wt % to 20 wt %, based on the total weight of the positive electrode active material layer.

[0107] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, wherein the positive electrode slurry has a solid content of 40wt% to 80wt%, and the viscosity at room temperature is adjusted to 5000mPa·s to 25000mPa·s, the positive electrode slurry is coated on both sides of the positive electrode collector, and after drying, it is cold-pressed by a cold rolling mill to form a positive electrode sheet.

[0108] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0109] As a non-limiting example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0110] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. Among them, in the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0111] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery known in the art.

[0112] As a non-limiting example, the negative electrode active material of the lithium ion secondary battery may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Silicon-based materials may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0113] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0114] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0115] In some embodiments, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0116] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt%~60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000mPa·s~10000mPa·s.

[0117] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0118] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0119] In some embodiments, the electrolyte salt of the lithium ion secondary battery may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0120] In some embodiments, the solvent may include one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE).

[0121] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0122] In some embodiments, the additive in the electrolyte may include, but is not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.

[0123] In some embodiments, the lithium-ion secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0124] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0125] In some embodiments, the thickness of the isolation film is 6 μm to 40 μm, and may be 12 μm to 20 μm.

[0126] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0127] In some embodiments, the lithium-ion secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0128] In some embodiments, the outer packaging of the lithium ion secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and further, non-limiting examples of plastic may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0129] A lithium-ion secondary battery includes at least one battery cell. A lithium-ion secondary battery may include one or more battery cells.

[0130] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.

[0131] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.

[0132] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0133] In some embodiments, the battery cells 5 can be assembled into a battery module. The number of battery cells 5 contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0134] In the battery module, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0135] Optionally, the battery module may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0136] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0137] The battery pack may include a battery box and a plurality of battery modules disposed in the battery box. The battery box includes an upper box body and a lower box body, and the upper box body can be covered on the lower box body to form a closed space for accommodating the battery modules. The plurality of battery modules can be arranged in the battery box in any manner.

[0138] In addition, the present application also provides an electrical device, which includes at least one of the lithium-ion secondary battery, battery module, or battery pack provided in the present application. The lithium-ion secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.

[0139] As an electrical device, a lithium-ion secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0140] Figure 3 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of lithium-ion secondary batteries, a battery pack or a battery module can be used.

[0141] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0142] The following are some examples.

[0143] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the present application will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0144] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0145] Embodiment 1:

[0146] (1) Preparation of positive electrode

[0147] (1.1) 0.19 g of hexamethyldisilazane (HMDS) and 0.95 g of SiO2 particles were stirred in anhydrous ethanol at 65°C for 2.5 h to modify the surface of the SiO2 particles, and then dried to obtain surface-modified SiO2; then mixed with 9.5 g of styrene (ST), 9.5 g of methyl methacrylate (MMA), and 9.5 g of butyl acrylate (BA) emulsion to form a Pickering emulsion; the above Pickering emulsion was reacted at 80°C for 1 h under the action of 0.532 g of initiator potassium persulfate (KPS) to prepare a SiO2-modified polyacrylate adhesive.

[0148] The Dv50 particle size of the SiO2 particles is 1 μm; the weight average molecular weight of the polyacrylate in the SiO2 modified polyacrylate binder is 150,000 Daltons, and the mass fraction of SiO2 in the binder is 5%.

[0149] (1.2) The positive electrode active material LiFePO4, the conductive agent carbon black (Super P), the SiO2 modified polyacrylate binder prepared above and the dispersant SEBS are mixed evenly in a proper amount of NMP at a mass ratio of 96.5:1:2:0.5 to obtain a positive electrode slurry; the positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing, striping, cutting and other processes. The solid content of the positive electrode slurry is 65%; the single-sided coating surface density of the positive electrode slurry is 25 mg / cm 2 .

[0150] (2) Preparation of negative electrode

[0151] The negative electrode active material artificial graphite, thickener sodium carboxymethyl cellulose, adhesive styrene butadiene rubber, and conductive agent carbon black (Super P) were mixed in a mass ratio of 97:1:1:1, and deionized water was added to obtain the negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry was evenly coated on the double-sided surface of the negative electrode current collector copper foil; the copper foil was dried at room temperature and transferred to a 120°C oven for 1 hour, and then cold pressed and cut to obtain the negative electrode sheet. The solid content of the negative electrode slurry is 50%; the single-sided coating surface density of the negative electrode slurry is 12mg / cm 2 .

[0152] (3) Isolation film

[0153] A 12 μm thick polypropylene film was selected as the isolation film.

[0154] (4) Electrolyte

[0155] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed at a mass ratio of 30:70 to obtain an organic solvent, and fully dried LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a LiPF6 concentration of 1 mol / L.

[0156] (5) Battery assembly

[0157] The positive electrode sheet, negative electrode sheet and isolation film are made into an electrode assembly through a winding process, and the electrode assembly is loaded into the battery outer packaging, and then baked at 80°C to remove water, and then the electrolyte is injected and sealed. After standing, hot and cold pressing, formation, clamping, capacity division and other processes, a lithium-ion secondary battery is obtained.

[0158] Embodiment 2:

[0159] This embodiment is basically the same as embodiment 1, except that: in step (1.1), 0.19 g of hexamethyldisilazane (HMDS) and 0.95 g of TiO2 particles are stirred in anhydrous ethanol at 65°C for 2.5 h to modify the surface of the TiO2 particles, and then dried; then mixed with 9.5 g of styrene (ST), 9.5 g of methyl methacrylate (MMA), and 9.5 g of butyl acrylate (BA) emulsion to form a Pickering emulsion; the above Pickering emulsion is reacted at 80°C for 1 h under the action of 0.532 g of initiator potassium persulfate (KPS) to prepare a TiO2 modified polyacrylate binder.

[0160] The Dv50 particle size of the TiO2 particles is 1 μm; the weight average molecular weight of the polyacrylate in the TiO2-modified polyacrylate binder is 150,000 Daltons, and the mass fraction of TiO2 in the binder is 5%.

[0161] Embodiment 3:

[0162] This embodiment is basically the same as embodiment 1, except that: in step (1.1), the surface-modified SiO2 particles are mixed with 9.5 g of styrene (ST), 9.5 g of methyl methacrylate (MMA), and 9.5 g of butyl acrylate (BA) emulsion to form a Pickering emulsion; the above Pickering emulsion is reacted at 80°C for 1 hour under the action of 0.3 g of initiator potassium persulfate (KPS) to prepare a SiO2 modified polyacrylate adhesive.

[0163] Wherein, the weight average molecular weight of the polyacrylate in the SiO2 modified polyacrylate binder is 300,000 Daltons.

[0164] Embodiment 4:

[0165] This embodiment is basically the same as embodiment 1, except that: in step (1.1), the surface-modified SiO2 particles are mixed with 9.5 g of styrene (ST), 9.5 g of methyl methacrylate (MMA), and 9.5 g of butyl acrylate (BA) emulsion to form a Pickering emulsion; the above Pickering emulsion is reacted at 80°C for 1 hour under the action of 0.18 g of initiator potassium persulfate (KPS) to prepare a SiO2 modified polyacrylate adhesive.

[0166] The weight average molecular weight of the polyacrylate in the SiO2 modified polyacrylate binder is 400,000 Daltons.

[0167] Embodiment 5:

[0168] This embodiment is basically the same as embodiment 1, except that: in step (1.1), 0.38 g of hexamethyldisilazane (HMDS) and 1.9 g of SiO2 particles are stirred in anhydrous ethanol at 65°C for 2.5 h to modify the surface of the SiO2 particles, and then dried; then mixed with 9.5 g of styrene (ST), 9.5 g of methyl methacrylate (MMA), and 9.5 g of butyl acrylate (BA) emulsion to form a Pickering emulsion; the above Pickering emulsion is reacted at 80°C for 1 h under the action of 0.532 g of initiator potassium persulfate (KPS) to prepare a SiO2 modified polyacrylate adhesive.

[0169] Wherein, the mass fraction of SiO2 in the SiO2 modified polyacrylate binder is 10%.

[0170] Embodiment 6:

[0171] This embodiment is basically the same as embodiment 1, except that: in step (1.1), 0.57 g of hexamethyldisilazane (HMDS) and 2.85 g of SiO2 particles are stirred in anhydrous ethanol at 65°C for 2.5 h to modify the surface of the SiO2 particles, and then dried; then mixed with 9.5 g of styrene (ST), 9.5 g of methyl methacrylate (MMA), and 9.5 g of butyl acrylate (BA) emulsion to form a Pickering emulsion; the above Pickering emulsion is reacted at 80°C for 1 h under the action of 0.532 g of initiator potassium persulfate (KPS) to prepare a SiO2 modified polyacrylate adhesive.

[0172] Among them, the mass fraction of SiO2 in the SiO2 modified polyacrylate binder is 15%.

[0173] Embodiment 7:

[0174] This embodiment is basically the same as embodiment 1, except that: in step (1.1), 0.76 g of hexamethyldisilazane (HMDS) and 3.8 g of SiO2 particles are stirred in anhydrous ethanol at 65°C for 2.5 h to modify the surface of the SiO2 particles, and then dried; then mixed with 9.5 g of styrene (ST), 9.5 g of methyl methacrylate (MMA), and 9.5 g of butyl acrylate (BA) emulsion to form a Pickering emulsion; the above Pickering emulsion is reacted at 80°C for 1 h under the action of 0.532 g of initiator potassium persulfate (KPS) to prepare a SiO2 modified polyacrylate adhesive.

[0175] Among them, the mass fraction of SiO2 in the SiO2 modified polyacrylate binder is 20%.

[0176] Embodiment 8:

[0177] This embodiment is basically the same as Embodiment 1, except that the Dv50 particle size of the SiO2 particles in step (1.1) is 5 μm.

[0178] Embodiment 9:

[0179] This embodiment is basically the same as Embodiment 1, except that in step (1.2), the mass ratio of the positive electrode active material LFP, the conductive agent carbon black (Super P), the SiO2 modified polyacrylate binder and the dispersant SEBS is 96.5:1.2:1.8:0.5.

[0180] Embodiment 10:

[0181] This embodiment is basically the same as Embodiment 1, except that in step (1.2), the mass ratio of the positive electrode active material LFP, the conductive agent carbon black (Super P), the SiO2-modified polyacrylate binder and the dispersant SEBS is 96.5:2:1:0.5.

[0182] Embodiment 11:

[0183] This embodiment is basically the same as Embodiment 1, except that in step (1.2), the mass ratio of the positive electrode active material LFP, the conductive agent carbon black (Super P), the SiO2-modified polyacrylate binder and the dispersant SEBS is 96.5:1.2:2:0.3.

[0184] Embodiment 12:

[0185] This embodiment is basically the same as Embodiment 1, except that in step (1.2), the mass ratio of the positive electrode active material LFP, the conductive agent carbon black (Super P), the SiO2-modified polyacrylate binder and the dispersant SEBS is 96.5:1.4:2:0.1.

[0186] Embodiment 13:

[0187] This embodiment is basically the same as embodiment 1, except that the dispersant in step (1.2) is BYK-110 phosphate ester dispersant.

[0188] Embodiment 14:

[0189] This embodiment is basically the same as embodiment 1, except that: in step (1.1), isooctyl acrylate is used instead of butyl acrylate to prepare SiO2 modified polyacrylate binder; in step (1.2), lithium iron manganese phosphate LiMn is used 0.6 Fe 0.4 PO4 replaces LiFePO4 as the positive electrode active material.

[0190] Comparative Example 1:

[0191] This comparative example is basically the same as Example 1, except that: the preparation method of the positive electrode sheet in step (1) is as follows: the positive electrode active material LiFePO4, the conductive agent carbon black (Super P), the polyacrylate binder and the dispersant SEBS are mixed uniformly in an appropriate amount of NMP according to a mass ratio of 96.5:1:2:0.5 to obtain a positive electrode slurry, wherein the weight average molecular weight of the polyacrylate binder is 150,000; the above-mentioned positive electrode slurry is coated on the double-sided surface of the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained by drying, cold pressing, slitting, cutting and other processes. The polyacrylate binder is prepared by mixing 9.5g of styrene (St), 9.5g of methyl methacrylate (MMA) and 9.5g of butyl acrylate (BA) to form an emulsion; the above-mentioned emulsion is reacted at 80°C for 1h under the action of 0.532g of initiator potassium persulfate (KPS).

[0192] Comparative Example 2:

[0193] This comparative example is basically the same as Example 1, except that: step (1.1) is not provided; SiO2-modified polyacrylate binder is not used in the positive electrode slurry of step (1.2); the positive electrode active material LFP, conductive agent carbon black (Super P), SiO2, polyacrylate binder and dispersant SEBS are mixed uniformly in an appropriate amount of NMP in a mass ratio of 96.5:1:0.1:1.9:0.5 to obtain a positive electrode slurry.

[0194] The polyacrylate adhesive was prepared by the following method: 9.5 g of styrene (ST), 9.5 g of methyl methacrylate (MMA), and 9.5 g of butyl acrylate (BA) were mixed in an emulsion, and reacted at 80° C. for 1 h under the action of 0.532 g of initiator potassium persulfate (KPS) to prepare the polyacrylate adhesive.

[0195] Test method:

[0196] (1) Pole brittleness test

[0197] Take a 20mm×100mm (longitudinal) sample of the prepared positive electrode sheet and sample along the rolling direction of the sheet; place the pre-folded experimental sheet on the test bench and roll it with a 2kg cylindrical roller. After each rolling, observe whether the sheet is light-transmissive. When the sheet is light-transmissive, record the corresponding rolling times. The rolling times represent the flexibility of the sheet. The greater the rolling times, the better the flexibility.

[0198] (2) Electrode mechanical properties test

[0199] (2.1) Adhesion test

[0200] The prepared positive electrode sheet is cut into test specimens of 20mm×100mm size for later use; one side of the double-sided tape is adhered to the surface of the steel plate, and the other side is adhered to the positive electrode sheet to be tested, and compacted with a pressure roller to make it completely fit with the sheet; one end of the current collector is bent in the opposite direction with a bending angle of 180°; a high-speed rail tensile testing machine is used for testing, one end of the steel plate is fixed to the lower fixture of the tensile testing machine, and the bent end of the current collector is fixed to the upper fixture, the angle of the current collector is adjusted to ensure that the upper and lower ends are in a vertical position, and the sample is stretched at a speed of 50mm / min until the active material layer is completely peeled off from the surface of the current collector, the displacement and force in the process are recorded, and the force when the force is balanced is taken as the bonding force of the sheet.

[0201] (2.2) Cohesion test

[0202] The prepared positive electrode sheet is cut into test specimens of 20mm×100mm size for later use; one side of the double-sided tape is adhered to the surface of the steel plate, and the other side is adhered to the positive electrode sheet to be tested, and compacted with a roller to make it completely fit with the sheet; a special tape for cohesion test is adhered to the other side of the sheet and compacted with a roller; one end of the special tape for cohesion is bent in reverse with a bending angle of 180°; a high-speed rail tensile testing machine is used for testing, one end of the steel plate is fixed to the clamp below the tensile testing machine, the bent end of the current collector is fixed to the clamp above, the angle of the current collector is adjusted to ensure that the upper and lower ends are in a vertical position, and then the sample is stretched at a speed of 50mm / min until the active material layer is completely peeled off from the surface of the current collector, the displacement and force in the process are recorded, and the force when the force is balanced is taken as the cohesion of the sheet.

[0203] (3) Battery DCR test

[0204] Let the battery cell stand for 10 minutes, charge to 3.65V at 1 / 3C constant current, then charge to 0.05C at constant voltage and let it stand for 30 minutes; then discharge to 2.5V at 1C to get capacity C1; let it stand for 30 minutes, then discharge to 0.5C1 at 1 / 3C, and measure the battery cell voltage V0 after standing for 30 minutes; then discharge at 3C for 30S and measure the battery cell V1 to calculate DCR, DCR= (V0-V1) / 3C.

[0205] (4) Battery rate performance test

[0206] Let the battery cell stand for 10 minutes, charge to 3.65V at 1 / 3C constant current, then adjust the voltage to 0.05C, let it stand for 30 minutes, and discharge to 2.5V at 1 / 3C to obtain capacity C1; then charge to 3.65V at 1 / 3C constant current, adjust the voltage to 0.05C, let it stand for 30 minutes, and discharge to 2.5V at 1C to obtain capacity C2; then charge to 3.65V at 1 / 3C constant current, adjust the voltage to 0.05C, let it stand for 30 minutes, and discharge to 2.5V at 2C to obtain capacity C3. 1C capacity retention rate = C2 / C1×100%; 2C capacity retention rate = C3 / C1×100%.

[0207] (5) Test on the mass ratio of inorganic materials in inorganic material modified polyacrylate binder

[0208] X-ray photoelectron spectroscopy XPS and energy dispersive spectrometer EDS are used to detect the characteristic elements of inorganic fillers in the binder and quantitatively calculate the mass proportion of inorganic materials.

[0209] (6) Weight average molecular weight test

[0210] The weight average molecular weight of the polymer was measured using gel permeation chromatography.

[0211] (7) Dv50 particle size test of inorganic materials

[0212] The Dv50 particle size of inorganic materials was measured using a laser particle size analyzer.

[0213] The battery parameters of the above embodiments and comparative examples are shown in Table 1, and the performance data are shown in Table 2. In the table, the amount of binder refers to the mass fraction of the binder in the positive electrode active material layer; the inorganic particle content refers to the mass fraction of the inorganic particles in the inorganic material modified polyacrylate binder. The weight average molecular weight, inorganic particle content and inorganic particle Dv50 in Table 1 are all rounded values.

[0214] Table 1

[0215]

[0216] Table 2

[0217]

[0218] It can be seen from Table 1 and Table 2 that the lithium ion secondary batteries of the embodiments of the present application have lower internal resistance and better dynamic performance. The positive electrode slurry of the lithium ion secondary batteries of Comparative Examples 1 and 2 does not use inorganic material modified polyacrylate binder, and its internal resistance is higher and the dynamic performance is poor.

[0219] The above description of various embodiments tends to emphasize the differences between the various embodiments. The same or similar parts can be referenced to each other, and for the sake of brevity, they will not be repeated in this article.

[0220] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A lithium ion secondary battery, characterized in that: The invention comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises a lithium-containing phosphate and an inorganic material-modified polyacrylate binder; The inorganic material modified polyacrylate binder comprises a polyacrylate polymer and inorganic particles, at least a portion of the polyacrylate polymer is grafted onto the surface of the inorganic particles; the polyacrylate polymer comprises a structural unit derived from an acrylic acid ester monomer.

2. The lithium ion secondary battery according to claim 1, characterized in that: The acrylic acid ester monomer includes one or more of methyl methacrylate, butyl acrylate or isooctyl acrylate.

3. The lithium ion secondary battery according to claim 2, characterized in that: The mass percentage of the structural unit derived from the acrylic acid ester monomer in the acrylic acid ester polymer is 60% to 80%.

4. The lithium ion secondary battery according to claim 1, characterized in that: The polyacrylate polymer further includes a structural unit derived from a first monomer, wherein the first monomer includes one or more of styrene or acrylonitrile.

5. The lithium ion secondary battery according to claim 4, characterized in that: The mass percentage of the structural unit derived from the first monomer in the polyacrylate polymer is 20% to 40%.

6. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that The weight average molecular weight of the polyacrylate polymer is 150,000 Daltons to 400,000 Daltons.

7. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that The inorganic particles include one or more of titanium dioxide, silicon dioxide, calcium stearate or aluminum oxide.

8. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that The mass fraction of the inorganic particles in the inorganic material modified polyacrylate binder is 5% to 20%.

9. The lithium ion secondary battery according to claim 8, characterized in that: The mass fraction of the inorganic particles in the inorganic material modified polyacrylate binder is 10% to 15%.

10. The lithium ion secondary battery according to any one of claims 1 to 5 and 9, characterized in that: Based on the total mass of the positive electrode active material layer being 100%, the mass fraction of the inorganic material modified polyacrylate binder is 1% to 2%.

11. The lithium ion secondary battery according to any one of claims 1 to 5 and 9, characterized in that: The positive electrode active material layer further includes a dispersant, and the dispersant includes one or more of a phosphate ester dispersant and a styrene-ethylene / butylene-styrene block copolymer dispersant.

12. The lithium ion secondary battery according to claim 11, characterized in that: Based on the total mass of the positive electrode active material layer being 100%, the mass fraction of the dispersant is 0.1% to 0.5%.

13. The lithium ion secondary battery according to claim 12, characterized in that: Based on the total mass of the positive electrode active material layer being 100%, the mass fraction of the dispersant is 0.3% to 0.5%.

14. The lithium ion secondary battery according to any one of claims 1 to 5, 9, 12 to 13, characterized in that: Based on the total mass of the positive electrode active material layer being 100%, the mass fraction of the lithium-containing phosphate is 95% to 99%.

15. The lithium ion secondary battery according to any one of claims 1 to 5, 9, 12 to 13, characterized in that: The lithium-containing phosphate includes one or more of lithium iron phosphate, lithium manganese phosphate or lithium manganese iron phosphate.

16. A method for preparing a lithium ion secondary battery, characterized in that: The following steps are involved: A lithium-containing phosphate, an inorganic material-modified polyacrylate binder and a solvent are mixed to obtain a positive electrode slurry; the inorganic material-modified polyacrylate binder comprises a polyacrylate polymer and inorganic particles, at least a portion of the polyacrylate polymer is grafted onto the surface of the inorganic particles; the polyacrylate polymer comprises a structural unit derived from an acrylic acid ester monomer; Placing the positive electrode slurry on a positive electrode current collector and drying the positive electrode to obtain a positive electrode sheet; and The positive electrode sheet, the separator and the negative electrode sheet are stacked so that the separator is disposed between the positive electrode sheet and the negative electrode sheet to obtain an electrode assembly, and the electrode assembly is made into a secondary battery.

17. The method for preparing a lithium ion secondary battery according to claim 16, characterized in that: The preparation method of the inorganic material modified polyacrylate binder comprises the following steps: The inorganic particles are surface modified by using a silane coupling agent; The surface-modified inorganic particles are mixed with an acrylic ester monomer, a first monomer, and an initiator to obtain the inorganic material-modified polyacrylate binder after reaction.

18. The method for preparing a lithium ion secondary battery according to claim 17, characterized in that: The preparation method satisfies one or more of the following (1) to (4): (1) The silane coupling agent includes one or more of hexamethyldisilazane, γ-aminopropyltriethoxysilane or γ-glycidyloxypropyltrimethoxysilane; (2) The initiator is a free radical polymerization initiator, and the initiator includes one or more of potassium persulfate, azobisisobutyronitrile or benzoyl peroxide; (3) The acrylic acid ester monomer includes one or more of methyl methacrylate, butyl acrylate or isooctyl acrylate; (4) The first monomer includes one or more of styrene or acrylonitrile.

19. The method for preparing a lithium ion secondary battery according to any one of claims 16 to 18, characterized in that: The preparation method satisfies one or more of the following (1) to (2): (1) The inorganic particles include one or more of titanium dioxide, silicon dioxide, calcium stearate or aluminum oxide; (2) The Dv50 particle size of the inorganic particles is 1 μm to 5 μm.

20. An electrical device, characterized in that: The invention comprises one or more of the lithium ion secondary battery according to any one of claims 1 to 15 or the lithium ion secondary battery prepared by the method for preparing the lithium ion secondary battery according to any one of claims 16 to 19.

Citation Information

Patent Citations

  • Reactive-group-containing graft copolymer and preparation method and application thereof

    CN108409922A

  • Emulsion type binder containing inorganic / organic core-shell structure and lithium ion battery

    CN111048786A

  • Surface modified electrode, preparation method and use in electrochemical cell

    CN115136359A

  • Binder for positive pole piece, positive pole piece and electrochemical device

    CN115692716A

  • Positive electrode binder and preparation method thereof, electrode assembly, battery monomer, battery and electric device

    CN118412470A

Cited By

  • Lithium-ion secondary battery and preparation method therefor, and electric device

    WO2026103309A1

  • Battery cell and preparation method therefor, battery device and electric device

    WO2026174999A1